PENGARUH ASET BERGERAK TERHADAP PENDAPATAN PT GARUDA INDONESIA (PERSERO) TBK TAHUN 2015-2019 (STUDI ARMADA PENERBANGAN) - Rosalia Cantika Gian; Saad Noor (POLITEKNIK PIKSI GANESHA, 2023)
This study aims to analyze the effect of the fleet on Garuda Indonesia's annual revenue. The method used is correlative quantitative method in order to get an overview of the influence of the fleet on annual revenue at Garuda Indonesia. The analytical method used is correlation coefficient analysis using Pearson Product Moment, determination analysis to determine the magnitude of the influence of the fleet on Garuda Indonesia's revenue, and simple linear regression analysis complemented by descriptive statistical analysis. From the results of the analysis, it was found that the correlation coefficient with the Pearson Correlation value was 0.941 which was classified as very strong and the determinant coefficient or the magnitude of the influence of the fleet on revenue was 0.886 or 88.6% which was classified as very strong. In this case, the addition of one fleet unit will increase the company's revenue by the value of the regression coefficient or by 3.493 (in tens of millions of USD). The results of the descriptive statistical analysis obtained an overview of the average value, maximum value, minimum value and standard deviation for each variable.